Cosmetic crimes in dromedary camels: a critical overview on these illegal manipulations and its hidden consequences - Tharwat, Mohamed (Frontiers in Veterinary Science, 2025)
This review highlights the emerging issue of illegal tampering in dromedary camels, particularly in the context of camel festivals where aesthetic alterations are performed to enhance appearance. These manipulations—often conducted by unqualified individuals—raise serious ethical and animal welfare concerns. Common techniques include mechanical and chemical modifications such as lip stretching, use of local anesthetics to alter facial expression, ear trimming, and injections of substances like silicone, fillers, and botulinum toxin (Botox) to modify head profiles. Hormonal treatments, including testosterone and growth hormone, are administered to induce exaggerated physical traits, often at the cost of fertility and health. Detection of tampering is increasingly challenging due to evolving methods and requires experienced personnel. Visual assessment remains the primary diagnostic step, followed by imaging techniques (e.g., ultrasonography, radiography, thermography) and hormonal assays. Economically, tampering distorts market values by misleading buyers on key animal traits, contributing to significant information asymmetry and undermining pastoral economies. It also introduces serious welfare issues, often carried out without veterinary oversight, resulting in pain, infection risk, and long-term functional impairments. Beyond health and economic implications, tampering undermines cultural integrity, erodes trust in livestock markets, and threatens food security in camel-dependent communities. Addressing this issue requires a multidisciplinary strategy involving scientific research, policy enforcement, community engagement, and education. Standardized inspection prostocols and mandatory certification can strengthen veterinary oversight and deter malpractice. In conclusion, the rise of illegal tampering in dromedary camels presents complex challenges to animal welfare, market integrity, and societal trust. A coordinated and ethically grounded response is essential to safeguard both animal and human livelihoods.